Investigation of acoustic radiation force to clean stone fragments - Lim, Clement Jun Xian (2017)
Extracorporeal Shockwave Lithotripsy (ESWL) is used to break down kidney stones into small fragments that are able to travel through the urinary tract and subsequently dispelled from the body together with the urine stream. However, there may be small pieces of the kidney stones that will be stuck in certain areas of the kidney. The small pieces that are stuck can possibly be removed by applying acoustic radiation force from a transducer to move the stuck pieces away from the kidney. Studies have been done on the radiation force produced by an acoustic beam and how it will affect a sphere submerged in a fluid. In this report, an experiment is set up to investigate and study the acoustic radiation force acting on a submerged sphere by applying an acoustic beam to the submerged sphere.